Chapter Influences et interactions entre Santa Maria Novella et la commune de Florence. Une étude de cas: les sermons de Remigio de' Girolami (1295-1301) - Carron, Delphine (Reti Medievali E-Book, 2020)
At the turn of the fourteenth century (1295-1301), the Florentine Dominican Remigio de' Girolami produced a collection of essential texts connected to events in Florentine politics that present the testimony of a well-informed intellectual directly involved in the Communal crises. This article proposes to analyze, as a case study, the influence of Remigio's five sermons on Florentine communal life. His preaching in reaction to the crises shaking Florence happened in dialogue with the institutions and citizens of the Commune. It bears witness to the interactions between Santa Maria Novella and the city of Florence and contributes to the development of the political philosophy of its time.